Pengaruh Kenaikan Harga BBM terhadap Permintaan angkot di Kota Medan Tahun 2023 - Awaliyah Matondang, Khairani; Graciela Sembiring; Safira, Vivi; Lumban Batu, Selfiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to analyze the impact of rising fuel oil (BBM) prices on demand for urban traffic (angkot) in the city of Medan. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, observations and documents from various sources. The research results show that the increase in fuel prices has a negative impact on the demand for public transportation in the city of Medan. This negative impact can be seen in three aspects, namely the decline in community purchases.